Analysis of Calculation of Cost of Production Using the Full Costing Method - Ulum, Bustanul; Maulidayanti, Diah Wulan; Rusdiyanto, Rusdiyanto (Future Science, 2024)
The goal of the study is to investigate and demonstrate that, for Micro, Small, and Medium-Sized Businesses, applying the complete costing method for calculating manufacturing costs results in a more accurate computation. This study is crucial for entrepreneurs since it helps them determine the precise cost of manufacturing things and determines how much profit they should make. This study employs qualitative descriptive methods. The results of this study's comprehensive costing technique calculation of manufacturing costs for commodities are more accurate for use in micro, small, and medium-sized enterprises.